The Influence of Brand Awareness and Perceived Value on the Purchasing Decision of Yamaha NMAX Motorcycles (A Study on Yamaha NMAX Motorcycle Users in Kolaka Regency) - Wahida, Wahida; Andry Stepahnie Titing, Fitri Kumalasari, (YUME : Journal of Management, 2025)
This study examines the influence of brand awareness and perceived value on consumer purchasing decisions for Yamaha NMAX motorcycles in Kolaka Regency. Utilizing a quantitative research approach with an explanatory design, data were collected from 130 respondents through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that brand awareness has a significant and positive impact on purchasing decisions (β = 0.364, t = 3.377, p = 0.000), demonstrating that consumers who recognize and recall the Yamaha NMAX brand are more likely to choose it over competitors. Similarly, perceived value significantly affects purchasing decisions (β = 0.352, t = 3.479, p = 0.000), suggesting that consumers assess functional, emotional, and social benefits when making purchase choices. These findings highlight the crucial role of brand equity and consumer perception in shaping market behavior, reinforcing the necessity for integrated branding strategies and value-driven marketing approaches to sustain competitive advantage. This research contributes to the existing body of knowledge by providing empirical insights into the interplay between brand awareness, perceived value, and purchasing decisions in the Indonesian motorcycle market. Future research should explore additional moderating factors, such as consumer trust, lifestyle preferences, or competitive market conditions, to enhance the understanding of consumer decision-making processes. Keywords: Brand Awareness, Perceived Value, Purchasing Decisions, Consumer Behavior, Marketing Strategy